Enhancing Early Reading Skills in Elementary Students with Learning Difficulties Through RTI-Based Moveable Alphabet Media - Ranny Dwi Agustin; Pujaningsih Pujaningsih (AL-ISHLAH: Jurnal Pendidikan, 2025)
Early reading difficulties among first-grade students can hinder academic success if not addressed promptly. This study explores the effectiveness of a Response to Intervention (RTI)-based moveable alphabet media in improving early reading skills among students with learning difficulties in an Indonesian elementary school. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model across two cycles. Eight first-grade students at Anugerah Abadi 2 Bengalon Elementary School, identified with early reading challenges, participated in the intervention. The RTI-based instruction incorporated multisensory learning through the use of moveable alphabet media. Data were collected using observations, pre- and post-tests, and documentation. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically. The average reading ability increased from 30% in the pre-cycle to 67.5% in Cycle I and 92.5% in Cycle II. Initially, none of the students met the success criteria (≥80%), but by Cycle II, all students achieved it. Observations indicated increased student engagement, motivation, and independence in reading activities. The findings suggest that integrating multisensory media with the RTI framework significantly enhances early reading skills in students with learning difficulties. The structured and individualized approach allowed for targeted interventions based on ongoing assessments. The study supports the effectiveness of hands-on, differentiated instruction grounded in constructivist and multisensory learning theories.